1994
DOI: 10.1523/jneurosci.14-07-04185.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphorylation in desensitization of acetylcholine receptors expressed in Xenopus oocytes

Abstract: The nicotinic acetylcholine receptor (AChR) is a pentameric complex made up of four types of subunits in the stoichiometry alpha 2 beta gamma delta. These subunits have been shown to be differentially phosphorylated by cAMP-dependent protein kinase (PKA) protein kinase C, and a protein tyrosine kinase. A variety of studies have suggested that phosphorylation of the AChR in vitro and in vivo regulates the rate of desensitization of the receptor. In this study we have used site-specific mutagenesis and patch-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
3
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 37 publications
0
43
3
1
Order By: Relevance
“…It is well established that protein phosphorylation plays an important role in various neuroreceptors (Huganir and Greengard, 1990;Hoffman et al, 1994). Our experiments with the cortical neuron NMDA receptors indicated that PKC inhibition prevented galantamine potentiation but PKA inhibition did not.…”
Section: Discussionmentioning
confidence: 51%
“…It is well established that protein phosphorylation plays an important role in various neuroreceptors (Huganir and Greengard, 1990;Hoffman et al, 1994). Our experiments with the cortical neuron NMDA receptors indicated that PKC inhibition prevented galantamine potentiation but PKA inhibition did not.…”
Section: Discussionmentioning
confidence: 51%
“…It is well established that protein phosphorylation plays an important role in various neuroreceptors (Huganir and Greengard, 1990;Hoffman et al, 1994). The majority of extracellular signals is mediated by the activation of membrane receptors that are coupled to transducer components located at the inner surface of the plasma membrane.…”
Section: Discussion Nnachr Subunit Dependence Of Nootropic Actionsmentioning
confidence: 99%
“…Furthermore, we studied ␣1-mutants in which the Ser-16 phosphorylated by PKC was replaced by negatively charged amino acids (Asp or Glu), which in other settings was shown to mimic constitutive phosphorylation (Hoffman et al, 1994;Pages et al, 1994). In each cell line, we analyzed the effects of the activation of phorbol ester-sensitive PKCs on the activity of Na,K-ATPase and the cell surface expression of Na,K-pumps under various experimental conditions.…”
Section: Introductionmentioning
confidence: 99%